1999 NBDB directory of registrants (as of June 15, 1999). - Philippines. National Book Development Board (Quezon City The Board, 1999)
It includes name of registrants (i.e. book publishers, book printers, book importers, wholesale booksellers, retail booksellers, forwarders, book authors, manufacturers of paper and other raw materials used in book publishing, importers of paper and other raw materials used in book publishing, publishers of non print information materials, wholesale suppliers of non-print information materials, retail supplier of non-print information materials and importers of non-print information materials) and data about their company.
Profiles of the registrants, as of June 15, 1999, to the National Book Development Board are compiled and arranged alphabetically in this Directory. It specifically includes list of registered book publishers, printers, authors and importers together with the wholesale and retail booksellers, forwarders, manufacturers and importers of raw materials used in book publishing, and lastly wholesale and retail suppliers and importers of non-print information materials.
Keywords: Publishers and publishing -- Philippines -- Directories; Booksellers and bookselling -- Philippines -- Directories